Aspek Pemasaran dari Produk Apple Terhadap Peningkatan Keuntungan Perusahaan Apple - Muhammad Irsyad Fadhil; Muhammad Miftah Al-Qahtani; Angga Dwi Prasetyo; Dini Vientianty (Pusat Riset dan Inovasi Nasional, 2025)
Apple has become a global highlight, particularly due to the products they release. Their products have generated significant profits for the company, especially in terms of marketing and customer loyalty to the Apple brand. This study uses a descriptive research approach. Apple has spent a considerable amount of money marketing their first products, driven by Steve Jobs as the company's leader when they launched their initial products. This is similar to their best-selling product, the iPhone, which has numerous strengths and weaknesses in the global market. Apple continues to strive to maintain a high standard for their iPhone compared to other companies. Therefore, companies engaging in marketing do not always need to spend large amounts, especially if their brand has been well-established for a long time and offers high-quality products.